The importance of social media on the FMCG market in Bangladesh - Joanna Bednarz; Patricia Orelly (International Journal of Management and Economics, 2020)
Objective: The purpose of this paper is twofold: first, to identify the general use of the internet and examples of main social media used by residents of Bangladesh and second, to discover their potential in building marketing communication between FMCG manufacturers and consumers. Methods: The research method used is a quantitative survey (face-to-face interviews) on the sample of 100 consumers conducted in September 2019 in Dhaka, the capital of Bangladesh. Key findings: The majority of respondents have regular access to internet facilities and mainly two social media platforms are used: Facebook and YouTube. Product informations are sent to these media platforms for making purchasing decisions of the products of the FMCG market. Mostly males and the youngest group of respondents show the highest interest to social media. Originality: This study contributes to the literature to develop the understanding of marketing communications from the perspective of FMCG manufacturers entering Bangladesh, as it is being the emerging market.
Keywords: D12; D83; L82; M31; 650; social media; marketing communication; Bangladesh; FMCG market